2002
DOI: 10.1051/0004-6361:20021088
|View full text |Cite
|
Sign up to set email alerts
|

The present-day chemical composition of the LMC

Abstract: Abstract. High-resolution observations of five OB-type main-sequence stars in the Large Magellanic Cloud (LMC) have been obtained with the UCLéchelle spectrograph on the 3.9-m Anglo-Australian Telescope. These spectra have been analysed using LTE model-atmosphere techniques, to derive stellar atmospheric parameters and chemical compositions. As these stars are located within the hydrogen burning main-sequence band, their surface abundances should reflect those of the present-day interstellar medium. Detailed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
115
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 29 publications
(48 reference statements)
8
115
3
Order By: Relevance
“…Russell & Bessell ( Regarding the B type stars, Rolleston et al (1993) and Rolleston et al (2002) found, from the analysis of 4 stars in the SMC and 5 stars in the LMC, respectively, mean values of metallicity of −0.8 ± 0.20 dex and −0.31 ± 0.04 dex. Korn et al (2000) In conclusion, the mean iron content of Cepheids, for the Magellanic Clouds, agree very well with the results obtained for non variable stars of similar age and stars that are Cepheid's progenitors.…”
Section: A Comparison With Different Stellar Populations In the Magelmentioning
confidence: 98%
“…Russell & Bessell ( Regarding the B type stars, Rolleston et al (1993) and Rolleston et al (2002) found, from the analysis of 4 stars in the SMC and 5 stars in the LMC, respectively, mean values of metallicity of −0.8 ± 0.20 dex and −0.31 ± 0.04 dex. Korn et al (2000) In conclusion, the mean iron content of Cepheids, for the Magellanic Clouds, agree very well with the results obtained for non variable stars of similar age and stars that are Cepheid's progenitors.…”
Section: A Comparison With Different Stellar Populations In the Magelmentioning
confidence: 98%
“…The Galactic photoelectric absorption was set to a column density of N H,GAL = 5.86 × 10 20 cm −2 (Dickey & Lockman 1990) with abundances according to Wilms et al (2000). The additional column density N H,LMC was left as a free parameter with abundances of 0.49 for elements heavier than helium (Rolleston et al 2002). All the uncertainties were calculated based on a Δχ 2 statistic of 2.706, equivalent to a 90% confidence level for one parameter of interest.…”
Section: Spectral Analysismentioning
confidence: 99%
“…In particular, the Large Magellanic Cloud (LMC) is actively forming stars in clusters and is an ideal laboratory for us to study star formation, particularly massive star formation in star clusters. In the LMC, the metallicity is a factor of $3 lower than in the solar neighborhood (Dufour et al 1982;Dufour 1984;Rolleston et al 2002). In addition, the visual extinctions are lower and the FUV field is stronger in the LMC than in the Milky Way (Israel et al 1986), characterizing the initial conditions of star formation.…”
Section: Introductionmentioning
confidence: 99%